Contact dermatitis – Pathomechanism and understanding of disease in clinical setting - Mathur, M; Kumari, S (Journal of College of Medical Sciences-Nepal, 2012)
According to the pathophysiological mechanisms involved, two major types of contact dermatitis recognized irritant contact dermatitis (ICD) and allergic contact dermatitis (ACD). The diagnosis of either ICD or ACD is mainly depending on comprehensive clinical data (history and physical examination) as well as by performing appropriate diagnostic patch testing. Two forms of contact dermatitis may differ in early phase of development but development of clinical dermatitis have similar mechanism confusing the clinician and differentiating between ICD and ACD is often difficult in the clinical setting. This review will allow practicing physician to adopt rational clinical approach and the implementation of scientific information for therapeutic as well as preventive strategies. Journal of College of Medical Sciences-Nepal,2011,Vol-7,No-4, 70-77 DOI: http://dx.doi.org/10.3126/jcmsn.v7i4.6816